Chitosan-Coated Liposomes Loaded with Green Tea Polyphenols Incorporated into Apple Juice: Characterization, Stability, in Vitro Digestion, and Sensory Analysis - Rivera-Tobar, D (Springer, 2025)
The potential of chitosan-coated liposomes loaded with green tea extract for apple juice fortification was evaluated. Their particle properties, including size, polydispersity index, zeta potential and encapsulation efficiency, were analyzed, as well as their physicochemical stability after pasteurization at 75 °C for 15 s and storage at 4 °C for 30 days. In addition, their in vitro digestion behavior and sensory perception were studied against a semi-trained panel. Formulations with 0.1%, 0.5%, and 1% chitosan were analyzed, combined with homogenization processes at 13,500 rpm for 2, 5, and 10 min. The results of the present study indicated that the best encapsulation condition was obtained with 0.1% chitosan and 10 min of homogenization, achieving a particle size of 479.94 nm, a polydispersity index of 0.44, a zeta potential of + 32.70 mV and an encapsulation efficiency of 61.31%. The fortified juice presented 1146.4 mg/L of polyphenols and 58.3% antioxidant capacity. Liposomes in juice under these conditions demonstrated greater thermal and 30-day storage stability. For in vitro digestion, free polyphenols were significantly affected by gastrointestinal conditions, reducing their bioaccessibility to 31.50%. In comparison, uncoated liposomes reached 44.10%, while those with 0.1% chitosan achieved 35.69%. Sensory evaluation showed no significant differences (P > 0.05) between fresh and fortified juice, suggesting that the incorporation of liposomes does not alter product perception. These findings support the viability of chitosan encapsulation as a strategy to improve the stability and bioaccessibility of polyphenols without affecting their sensory acceptability. © The Author(s), under exclusive licence to Springer Science+Business Media, LLC, part of Springer Nature 2025.